1997
DOI: 10.1093/brain/120.10.1805
|View full text |Cite
|
Sign up to set email alerts
|

A study of the performance of patients with frontal lobe lesions in a financial planning task

Abstract: It has long been argued that patients with lesions in the prefrontal cortex have difficulties in decision making and problem solving in real-world, ill-structured situations, particularly problem types involving planning and look-ahead components. Recently, several researchers have questioned our ability to capture and characterize these deficits adequately using just the standard neuropsychological test batteries, and have called for tests that reflect real-world task requirements more accurately. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(103 citation statements)
references
References 38 publications
5
92
0
6
Order By: Relevance
“…Although there exists a paucity of research related to the cognitive determinants of semantic planning, research concerning patients with frontal lobe damage has provided some initial data. Patients with frontal lobe damage exhibit difficulty in formulating both episodic plans (see above) and financial plans for others (78). It is important to point out that financial planning for others may incorporate both episodic and semantic features of planning (e.g., people may use their own experiences to formulate plans for others) (ref.…”
Section: Varieties Of Future Thinkingmentioning
confidence: 99%
“…Although there exists a paucity of research related to the cognitive determinants of semantic planning, research concerning patients with frontal lobe damage has provided some initial data. Patients with frontal lobe damage exhibit difficulty in formulating both episodic plans (see above) and financial plans for others (78). It is important to point out that financial planning for others may incorporate both episodic and semantic features of planning (e.g., people may use their own experiences to formulate plans for others) (ref.…”
Section: Varieties Of Future Thinkingmentioning
confidence: 99%
“…Patients with PFC lesions (and thus disruption of their SECs) should show deficits in ordering events into a coherent sequence. Patients with PFC damage have particular difficulty sequencing events,79 can generate a normal number of actions, but have difficulty ordering those actions into a coherent script,80,81 and appear to lose infrequently used SECs before frequently used (and thus overlearned) SECs 80,82. Patients with dementias affecting the frontal lobes typically demonstrate deficits in social behaviors with relative preservation of episodic memory, while patients with dementia initially affecting the medial temporal lobes (e.g., Alzheimer’s disease) typically demonstrate initial deficits in episodic memory with relative preservation of social behavior 83…”
Section: The Prefrontal Cortex (Pfc) In the Execution And Reinforcemementioning
confidence: 99%
“…In contrast, patients with frontal lobe damage usually have little difficulties in execution of simple familiar routines, but are unable to engage in behaviors that are weakly established and require understanding of a goal and the means to achieve it (Shallice et al, 1991). Several studies suggested that access to graded semantic representations in these patients is relatively spared: they have no difficulty in determining which events tend to co-occur in common realworld activities (Sirigu et al, 1995(Sirigu et al, , 1996; and they are selectively impaired in sequentially ordering uncommon or unfamiliar rather than routine event sequences (Sirigu et al, 1995;Goel et al, 1997).…”
Section: Two Semantic Neurocognitive Mechanisms Of Comprehension: a Hmentioning
confidence: 99%